Inovasi Eco Brick : Plang Nama Desa yang Ramah Lingkungan dan Unik - Agus Setiawan; Tiara Listiana; Lindawati Lindawati; Yunizir Djakfar; Rini Efrianti (Universitas 45 Surabaya, 2025)
This community service project aims to introduce and implement Eco brick innovation in creating a sustainable and unique village signboard in Persiapan Sinar Bhakti Village, OKU Regency. The issue faced is the underutilization of environmentally friendly recycled materials in creating public infrastructure such as village signboards. Additionally, Persiapan Sinar Bhakti Village does not yet have a village signboard, making this project essential for establishing the village's identity. The objective of this project is to raise awareness among the community about the importance of using eco-friendly materials and recycling plastic waste into useful products, such as a village signboard made from Eco brick. The method used in this project is training and guidance for the local community on how to make Eco bricks, which are then used to create the village signboard with the text